Human Resources based on Total Quality Management - Samsul Arifin; Didit Darmawan; Cahya Fajar Budi Hartanto; Abdul Rahman (Journal of Social Science Studies (JOS3), 2022)
Human resources owned by a company is the strength it has in order to be able to compete with other companies. company management will always create strategies to be able to create quality human resources. The strategy carried out will continue to move dynamically along with technological advances. One way to improve the quality of human resources is by implementing Total Quality Management or TQM. The application of TQM will provide many benefits for the company and the employees themselves. With TQM all aspects of the company such as leadership and employee training will be well planned and supervised. This study aims to determine the role of TQM in empowering human resources in companies. All expert opinions say that the implementation of TQM will have a positive impact on empowering the human resources they have. The disadvantage of implementing TQM is that the costs incurred are quite high. Management needs to think of more strategies in order to get a lot of benefits but not interfere with the company's financial situation.